Patients with suspected myocardial infarction: their test request patterns for clinical biochemistry in a British and a Canadian cardiac care unit. - Henderson, A R (1986)
The total number of routine clinical biochemistry tests requested for patients admitted to a coronary care unit with a diagnosis of "query myocardial infarction" were recorded over four to eight months. There were 156 sequential admissions in a British teaching hospital and 163 in a Canadian counterpart; the incidence of confirmed myocardial infarction was 53% and 50%, respectively. The pattern of tests ordered was substantially similar in each unit, unlike the rate of testing. For example, total creatine kinase was requested five times less often per patient in the British hospital than in the Canadian unit in cases of confirmed myocardial infarction (2.17 and 10.17, respectively; p less than 0.0001): the difference was much less, but still significant, when there was no infarction (2.01 and 3.55; p less than 0.0001). This study suggests a significant international difference in the use of clinical biochemistry services between coronary care units. Physicians (clinical and laboratory) need to be more critical of their use of protocols, which may prove wasteful of limited health care resources.